Analisis Yuridis Penegakan Hukum Kasus Peredaran Rokok Ilegal Menurut UU Bea Cukai - Muhammad Sofyan Sauri; Syarifuddin Syarifuddin; Ahmad Yunus (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of illegal cigarette circulation can still be found especially in Jember district. The characteristics of illegal cigarettes include the absence of excise stamps on the cigarette packs, attaching cigarette packs with fake excise tape or placing excise tape that is not in accordance with its intended use. The Directorate General of Customs and Excise has the authority to take action and investigate illegal cigarette distributors in accordance with Law Number 39 of 2007 concerning amendments to Law Number 11 of 1995 about excise. The purpose of this researcher is to find out the law enforcement process against illegal cigarette dealers in Jember Regency by the Jember Regenc KPPBC. This research method uses empirical legal research. Primary and secondary data obtained through interviews with staff of the prosecution and investigation section of the Jember Regency KPPBC. The data analysis method is descriptive qualitative. The results of this study are that law enforcement carried out by the Jember Regency KPPBC has not been able to be carried out optimally because in its implementation there are many obstacles such as a very wide illegal cigarette distribution network so that there isa lack of officers. However, these various obstacles can hopefully be overcome with existing efforts.